Functionalized Nanomaterials 2016
DOI: 10.5772/66218
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Carbon Nanotubes and Semiconductor Nanocrystals as Advanced Functional Material with Novel Optoelectronic Properties

Abstract: Semiconductor nanoparticles of very small size, or quantum dots, exhibit fascinating physical properties, completely different from their bulk varieties, mostly because of the quantum confinement effect. Due to their modified band structure, they particularly show attractive optoelectronic characteristics. Carbon nanotubes are a class of nanomaterials, which also possess wonderful optoelectronic properties and can revolutionize modern semiconductor technology to a great extent. Carbon nanotube fieldeffect tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Such structures enhance the efficiency of charge separation and greatly reduce the exciton recombination. , Functionalization of semiconductor nanoparticles (NPs) with a varying band gap on the SWCNT surface will produce a new class of functional materials with remarkable properties by combining characteristics of individual components. These nanocomposites are potentially useful in a wide range of advanced applications, in the field of chemical sensors, biosensors, and nanoelectronics …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such structures enhance the efficiency of charge separation and greatly reduce the exciton recombination. , Functionalization of semiconductor nanoparticles (NPs) with a varying band gap on the SWCNT surface will produce a new class of functional materials with remarkable properties by combining characteristics of individual components. These nanocomposites are potentially useful in a wide range of advanced applications, in the field of chemical sensors, biosensors, and nanoelectronics …”
Section: Introductionmentioning
confidence: 99%
“…Two mechanisms are proposed to explain the photo-interaction in SWCNTs: (I) The interband transition model is associated with a series of van Hove singularities in the one-dimensional (1D) electronic density of states. Electron–hole pairs are produced upon photoexcitation, and the lifetime of these carriers is long with spectral features in absorption and photoconductivity that match the optical transitions associated with the van Hove singularities. , (II) In the exciton model, photogenerated electron–hole pairs at energies lower than the direct band gap give rise to charge-neutral species that cannot contribute directly to photoconductivity unless a charge separation mechanism, such as a large bias, is provided . Instead, the excitons interact with the CNT lattice and dissociate thermally, thus enhancing the photoresponse of SWCNTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, seeded nanorods (sNRs) in photovoltaic devices and photodetectors have exhibited a highly efficient charge separation [7][8][9][10][11]. The combination of the high charge transport capabilities of CNTs with the optoelectronic flexibility of single component symmetric quantum dots (QDs) was studied for light-harvesting applications such as photovoltaic cells [12][13][14][15][16][17][18], photocatalysis [19,20], and light sensors [21][22][23][24][25][26][27][28][29][30]. Equivalently, Konstantatos et al [31] reported a large responsivity ∼10 7 A W −1 and photoconductive gain ∼10 8 in an analogous hybrid device comprised graphene and colloidal QDs.…”
Section: Introductionmentioning
confidence: 99%